Thermal degradation behavior of coffee residue in comparison with biomasses and its product yields from gasification - Suparin Chaiklangmuang (2018)
© 2014 Energy Institute. Published by Elsevier Ltd. All rights reserved. The thermal degradation behavior of coffee residue in comparison with that of several biomass samples and coffee residue steam catalytic gasification were investigated. Devolatilization was carried out using the thermogravimetric method, at temperatures ranging from 30 °C to 1000 °C. By and large, coffee residue decomposition was easier than that of other biomasses, but it was less than that of chicken feces; also, the devolatilization behaviors of the biomasses depended predominantly on the type of biomass. Steam catalytic gasification was carried out in the two-stage quartz-fixed bed that used Ni-loaded brown coal catalyst to produce fuel gases at low reaction temperatures, ranging from 500 °C to 650 °C, and at a steam pressure of 30 kPa. Particularly noteworthy was the fact that the total gas yield increased significantly with increase in temperature. According to Total Organic Carbon results, at temperatures above 550 °C, the light tar materials were almost constant. As evident from the results of the LY-Ni coal pyrolysis, at a catalytic bed temperature of 600 °C, there is a slight interfere of the LY-Ni catalyst in the biomass gasification yield, and it would be possible to take the advantage of brown coal to produce the gas products, H2, CO, CO2and CH4, from the coffee residue steam catalytic gasification.